2017
DOI: 10.1063/1.4982659
|View full text |Cite
|
Sign up to set email alerts
|

A computational study of the interaction of gaseous detonations with a compressible layer

Abstract: The propagation of two-dimensional cellular gaseous detonation bounded by an inert layer is examined via computational simulations. The analysis is based on the high-order integration of the reactive Euler equations with a one-step irreversible reaction. To assess whether the cellular instabilities have a significant influence on a detonation yielding confinement, we achieved numerical simulations for several mixtures from very stable to mildly unstable. The cell regularity was controlled through the value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 77 publications
9
41
1
Order By: Relevance
“…The unsteady 2-D simulations were performed using an inviscid formulation with detailed chemistry. Particulars about the numerical methods used, spatial and temporal discretizations as well as the parallelization methodology can be found in [16]. Briefly, we used time-operator splitting to couple the hydrodynamics to the chemistry together with directional splitting, along with a ninth-order monotonicity preserving interpolation in space, and a third order explicit Runge-Kutta in time.…”
Section: Detonation Modelsmentioning
confidence: 99%
“…The unsteady 2-D simulations were performed using an inviscid formulation with detailed chemistry. Particulars about the numerical methods used, spatial and temporal discretizations as well as the parallelization methodology can be found in [16]. Briefly, we used time-operator splitting to couple the hydrodynamics to the chemistry together with directional splitting, along with a ninth-order monotonicity preserving interpolation in space, and a third order explicit Runge-Kutta in time.…”
Section: Detonation Modelsmentioning
confidence: 99%
“…Instead, the rapid burn-out of non-reacted pockets by diffusive processes explains why the reaction zones remain substantially shorter. The effective reaction rates for the dynamics of cellular detonations extracted from these experiments can naturally find use in problems in which quasi-steady and stationary cellular detonation waves appear, for example in problems of detonations weakly confined by an inert layer (Reynaud et al 2017) as for rotating detonation engines. Future work should be devoted to this validation.…”
Section: Effective Reaction Models For Cellular Detonationsmentioning
confidence: 99%
“…In gases, real detonations are multi-dimensional and their reaction zone is often turbulent; deviations from the ZND model are substantial (Lee 2008;Shepherd 2009) and cannot be treated as perturbations. Analysis of unstable detonations revealed that although the structure is highly transient, it recovers qualita-tively a quasi-one-dimensional average structure analogous to the ZND structure, with an average sonic surface (Gamezo et al 1999;Radulescu et al 2007b;Reynaud et al 2017;Maxwell et al 2017). It thus appears that, with the appropriate kinetic description for the averaged fluid state and speed dictated by an effective rate of energy release, the ZND model with its extensions may be an appropriate framework to model real detonations at the macro-scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flame propagation and deflagration-to-detonation transition (DDT) have drawn extensive attention over the past years not only due to their destructive effects in the fire safety area such as mine explosion but also because of their potential applications in some propulsion systems, e.g., a pulsed detonation engine (PDE). [1][2][3][4][5][6][7][8] It is generally considered that the overall DDT process in a smooth tube basically involves three stages: first, flame acceleration and leading shock wave generation, then formation of the preheated zone ahead of the flame front, and finally, formation of a detonation wave (DW). 8,9 However, the quantitative theory and comprehensive mechanism of DDT remain still poorly understood as a result of its complicated combination of multiple highly nonlinear processes including interactions among flames, shocks, boundary layers, and turbulence.…”
Section: Introductionmentioning
confidence: 99%